Legal Protection and Employer Responsibility for Workers Who Do Not Have a Written Employment Agreement Based on Law no. 13 of 2003 - Anandasari Dinayah Anwar; J. Ronald Mawuntu; Doortje D. Turangan (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study aims to analyze the form of legal protection for workers who do not have a written employment agreement and the responsibilities of employers based on Law Number 13 of 2003 concerning Manpower. The research method used is normative legal research with a statute approach and a conceptual approach. The data used are in the form of primary, secondary, and tertiary legal materials analyzed qualitatively through literature studies. The results of the study indicate that even though the employment relationship is not made in the form of a written employment agreement, workers still receive legal protection as long as they have fulfilled the elements of an employment relationship, namely the existence of work, wages, and orders. Based on the provisions of Law Number 13 of 2003, an employment relationship that is not stated in a written employment agreement, especially a Fixed-Term Employment Agreement (PKWT), can be considered an Indefinite-Term Employment Agreement (PKWTT). Employers remain responsible for fulfilling workers' normative rights, such as payment of wages, employment social security, working hours, leave, occupational safety and health protection, and the provision of severance pay in the event of termination of employment in accordance with the provisions of laws and regulations. Thus, the existence of a written employment agreement provides legal certainty for both parties. However, the absence of a written employment agreement does not eliminate the employer's obligation to provide legal protection and fulfill workers' rights as stipulated in laws and regulations.